2020
DOI: 10.1145/3377478
|View full text |Cite
|
Sign up to set email alerts
|

Fake News Early Detection

Abstract: Massive dissemination of fake news and its potential to erode democracy has increased the demand for accurate fake news detection. Recent advancements in this area have proposed novel techniques that aim to detect fake news by exploring how it propagates on social networks. Nevertheless, to detect fake news at an early stage, i.e., when it is published on a news outlet but not yet spread on social media, one cannot rely on news propagation information as it does not exist. Hence, there is a strong need to deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(40 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…The results indicated that news focused on fake health information was often considered as bad messaging and that news based on the evidence of social influence was acceptable and respected. Furthermore, the study [19] proposed a theory-based model to early distinguish fake news. Based on the news content, the model detected fake news when it was published on news sites before spreading on social media platforms.…”
Section: Related Workmentioning
confidence: 99%
“…The results indicated that news focused on fake health information was often considered as bad messaging and that news based on the evidence of social influence was acceptable and respected. Furthermore, the study [19] proposed a theory-based model to early distinguish fake news. Based on the news content, the model detected fake news when it was published on news sites before spreading on social media platforms.…”
Section: Related Workmentioning
confidence: 99%
“…In the same vein, the work in [21] employed supervised learning techniques to detect fake news at an early stage, when no information exists about the spreading of the news on social media. Thus, the approach relies on the lexicon, syntax, semantics, and argument organization of a news item.…”
Section: Fake News and Bot Detectionmentioning
confidence: 99%
“…There is no consistent definition of fake news; its identification is complex and can sometimes be difficult to determine [ 12 , 27 , 29 - 31 ]. The definition of fake news can be as broad as improper information or stories [ 18 , 27 , 32 ], or as narrow as verifiably false articles deliberately published by the media [ 11 , 12 , 27 ], and anything in between [ 13 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…An automatic detection method could involve knowledge base retrieval systems [ 27 ], but breakthrough knowledge may be considered misinformation. Content style analysis is another automated method, based on the assumption that there is a certain pattern in intentional news [ 31 , 35 - 37 ], but outlets may evade detection by manipulating their writing style [ 27 ]. In this study, we employed a style-based approach to fake news detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation